Аналіз і порівняння засобів автоматизованого конфігурування пристроїв інфокомунікаційних мереж - Яковенко, К. О. (ХНУРЕ, 2024)
The automation of network equipment configuration has become essential for efficient infrastructure management in contemporary information and communication networks. Manual device configuration, particularly in large-scale networks, is time-consuming and labor-intensive, significantly increasing the likelihood of human error. Automation tools such as Ansible, Puppet, and SaltStack streamline the configuration and management of hundreds of devices simultaneously, reducing the time and effort needed to sustain infrastructure. These tools not only enhance configuration reliability but also support easier maintenance and scalability of networks. This work provides a comparative analysis of key automation tools to highlight their strengths and weaknesses and offers recommendations for selecting the most suitable solution.
Keywords: автоматизоване конфігурування пристроїв; мережні пристрої